PENGARUH KEBERADAAN MASYARAKAT TERHADAPKELESTARIAN POPULASI HARIMAU SUMATERA (Panthera tigris sumatrae) DI SEKITAR KAWASAN TAMAN NASIONAL BUKITTIGAPULUH (TNBT) DESA RANTAU LANGSAT - Wendy Fitrah; Defri Yoza; M. Mardhiansyah M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Bukit Tigapuluh National Park (BTNP) is an area who designated by the Minister of Forestry as a National Park with total area 127.698 ha based on decree No. 539/Kpt-II/1995. TNBT has a wealth of various types of wildlife, which Panthera tigris sumatraeis one of the wild animal that live with endanged status in BTNP. This is due to factors are always consider to occur because of the existence of society in the surrounding area of BTNP which resulting of increasing activity of the society. The aim of this study is to determinate the effect of the existence of society arround BTNP to Panthera tigris sumatrae population and to determine the role of society on the conservation of Panthera tigris sumatrae in BTNP. This study conducted using a descriptive qualitative design and involving 17 informans who recruited using purposive sampling and quoted sampling. The result showed that the existence of rural society in Rantau Langsat village who living arround BTNP is not affected the population of Panthera tigris sumatrae and then the society role of conservation of Panthera tigris sumatrae in BTNP is high enough. This indicates that the existence of society in Rantau Langsat village have been assist the preversation effort of Panthera tigris sumatrae population.Keyword : Effect, Society, Panthera tigris sumatrae, Population